Vermicomposting of chicken or quail manure with water hyacinth into valuable bio-fertiliser with earthworms. - Tan, Cassandra Lang Yee. (2012)
Significant amounts of organic waste are produced annually by poultry farms in Singapore and its disposal could be tackled by vermicomposting, a process that generates valuable bio-fertillisers. The present study reports on the use of earthworms, Eisenia fetida and Perionyx Excavatus, to convert chicken or quail manure mixed with water hyacinth into vermicompost. Six vermireactors with different treatments were carried out for 50 days. Baseline physico-chemical parameters for the starting raw materials were collected. The maximum and minimum worm biomass growth was reported in 10% chicken manure: 90% water hyacinth and 20% quail manure: 80% water hyacinth (w: w) ratios respectively. At the end of the experiment, vermicasts collected recorded an increase in total sodium, total phosphorus, iron and copper but a decrease in electrical conductivity. No particular trend was observed for pH, C/N ratio, total potassium and lead for all the vermireactors. Arsenic was detected in the vermireactor containing quail manure at end of the study. The vermireactor with optimum worm biomass production had the following parameters recorded at the end of experiment: pH= 8.07 0.08, electrical conductivity= 4.47 0.41 dS m-1 and C/N ratio= 17.8 1.5. The results indicated that chicken manure and water hyacinth can be used to produce bio-fertiliser.